Analysis of Salivary Cytokines in Retinopathy of Prematurity - Hwa-Shiu Wu; Hsin-Chun Huang; I-Lun Chen (Children)
Background/Objectives: This cohort study aimed to establish a correlation between salivary cytokines and retinopathy of prematurity (ROP) in premature neonates. Additionally, we sought to identify a minimally invasive method for cytokine detection in this population. Methods: We recruited premature neonates born at less than 34 weeks gestational age (GA), with no history of maternal or neonatal infections. Salivary samples were collected on their first (D1) and seventh (D7) days of life, and cytokine levels were measured using the MILLPLEXMAP Human multiplex assay. Results: A total of 125 neonates were included in the study, categorized into two groups based on the severity of ROP: None to Mild and Moderate to Severe. The salivary levels of interleukin (IL)-6, IL-8, vascular endothelial growth factor (VEGF), and tumor necrosis factor (TNF)-α on D1 and D7 were significantly higher in the Moderate to Severe ROP group compared to the None to Mild ROP group (p = 0.005, 0.004, 0.026, 0.018, 0.001, 0.007, 0.025, and 0.002, respectively). After adjusting for GA, the levels of IL-6 and VEGF on D7 were significantly elevated in the Moderate to Severe ROP group compared to the None to Mild ROP group (p = 0.024 and 0.016, respectively). Conclusions: This study establishes a novel, non-invasive method for the early prediction of ROP in premature neonates by correlating salivary cytokine levels in early life with the subsequent development of ROP.